Improvement of Panax notoginseng saponin accumulation triggered by methyl jasmonate under arbuscular mycorrhizal fungi - Dai, Hong-Yang; Zhang, Xing-Kai; Bi, Yue; Chen, Di; Long, Xian-Nv; Wu, Yue; Cao, Guan-Hua; He, Sen (Frontiers in Plant Science, 2024)
The main purpose of this study is to uncover the physiological and molecular mechanism of Panax notoginseng saponin accumulation triggered by methyl jasmonate (MeJA) under arbuscular mycorrhizal fungi (AMF) by determining physiological indices, high-throughput sequencing and correlation analysis. Physiological results showed that the biomass and saponin contents of P. notoginseng, the concentrations of jasmonic acids (JAs) and the key enzyme activities involved in notoginsenoside biosynthesis significantly increased under AMF or MeJA, but the interactive treatment of AMF and MeJA weakened the effect of AMF, suggesting that a high concentration of endogenous JA have inhibitory effect. Transcriptome sequencing results indicated that differential expressed genes (DEGs) involved in notoginsenoside and JA biosynthesis were significantly enriched in response to AMF induction, e.g., upregulated genes of diphosphocytidyl-2-C-methyl-d-erythritol kinases (ISPEs), cytochrome P450 monooxygenases (CYP450s)_and glycosyltransferases (GTs), while treatments AMF-MeJA and salicylhydroxamic acid (SHAM) decreased the abundance of these DEGs. Interestingly, a high correlation presented between any two of saponin contents, key enzyme activities and expression levels of DEGs. Taken together, the inoculation of AMF can improve the growth and saponin accumulation of P. notoginseng by strengthening the activities of key s 删除[行者]: are 删除[行者]: reveal 删除[行者]: ion 删除[行者]:enzymes and the expression levels of encoding genes, in which the JA regulatory pathway is a key link. This study provides references for implementing ecological planting of P. notoginseng, improving saponin accumulation and illustrating the biosynthesis mechanism.